Os sentidos do direito, do sindicato e da vida em disputa: resistências trabalhadoras e sindicais à transfobia e ao cissexismo no telemarketing - Flávio Malta Fleury (2020)
This thesis presents some of the contours and nuances of transphobia and cissexism reproduced in telemarketing companies in the metropolitan region of São Paulo. As well as the contours and nuances of some of the actions and activities conceived and lived to resist transphobia and cissexism proposed and developed by transgender women, transmen and non-binary people who worked in the segment, and also by the Union of Telemarketing Workers and Employees in Telemarketing Companies in the City of São Paulo and Greater São Paulo, Sintratel. In order to understand how the meanings of law, state, unions and life itself have been disputed and claimed by companies in the sector, transgender workers and union leaders, to reproduce or resist transphobia and cissexism in telemarketing companies. From the development of a multi-sited ethnography, in which the methods of participant observation, semi-structured interviews and document analysis were used, as well as from a review of interdisciplinary bibliography, composed of works from different areas of knowledge, such as law, philosophy, anthropology and sociology, this research develops reflections and feelings around workers’ and union’s resistances that demand recognition and respect for transgender identities, resistances that claim social, cultural, legal and economic conditions that will assure transgender people the possibilities of living their lives as they wish and how they do it without being victims of embarrassment, discrimination and violence. Workers’ and union’s resistances that challenge the normative, administrative and institutional domains of law and of the state, as well as the forms of organization and management of telemarketing companies, to demand new configurations for these domains, for these forms of business organization and management. So that they can live lives that are worth living.